EFEKTIVITAS SISTEM PENUKARAN SAMPAH MENJADI TABUNGAN DI BANK SAMPAH DAMAI KREATIF KELURAHAN PENGANTUNGAN - Muhamad Syahril Dewantara; Ganefi, S.H., M.Hum; Ahmad Sobari; Ikhsan Eka Putra; Lisa Febriana; Serli Defita; Puja Sri Wilujeng; Rika Putri Sanveri (UNIB Press, 2025)
This study aims to evaluate the effectiveness of the waste exchange system for savings at the Damai Kreatif Waste Bank in Pengantungan Village. The program was implemented through an educational and participatory approach during the Community Service Program (KKN). The results indicate an increase in community participation in sorting and depositing economically valuable inorganic waste, as well as economic benefits in the form of savings that assist household needs. The program also has a positive impact in reducing waste volume sent to the landfill. Challenges such as fluctuations in waste prices and the sustainability of the program post-KKN need to be addressed through capacity building and local government support. Overall, this system is effective in promoting community-based sustainable waste management.